Hidrólisis ácida de cascarilla de arroz para la generacion de azúcares reductores - Sigüencia Avila, Jorge Marcelo; Soler, Jaime; Menéndez, Miguel (Jornada de Jóvenes Investigadores del I3A, 2018)
Tests on hydrolysis reaction of rice husk to generate total reducing sugars (ART) have been carried out. Variables have been modified such as time, temperature, acid concentration and biomass concentration. Finally, the best result (ID A100) generated 92.9 mg ART / g Biomass.